Evaluation of tubal patency by sonosalpingography is as good as hysterosalpingography in infertile women - Lakshmi, C. Santhana; Sampath, Kumara; Vardani, Parvatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Tubal pathology is one of the causes of infertility in sub fertile couples. Therefore, evaluation of fallopian tubes forms an essential part of evaluation in a sub fertile woman. The aim of the study was to compare the efficacy of sonosalpingography which is a less invasive method when compared to hysterosalpingogram for evaluation of utero-tubal factor in females. Methods: A total of 95 patients 69 with primary infertility and 26 with secondary infertility attending our Obstetrics and Gynecology department were recruited for the study from June 2016 to July 2017. All the study subjects underwent Sonosalpingography on day 5th to 7th and Hysterosalpingography on 7th to 9th day of the menstrual cycle. Data was collected and compared to assess the sensitivity and specificity of sonosalpingography over hysterosalpingography. Statistical analysis was done by using SPSS software version 16.0. Results: Sonosalpingography (SSG) has 97% sensitivity and 94% specificity in comparison to hysterosalpingography (HSG). Analysis of the raw data gave positive predictive value of 98.3% and negative predictive value of 75%. From the results of this study it clear that there is no statistically significant difference (p = 0.237) between the results of the two methods (SSG and HSG). Conclusions: As sonosalpingogrpahy has high sensitivity and specificity and is less invasive. It should be used initially to assess tubal patency in cases of infertility. SSG is found to be a reliable, relatively less expensive diagnostic and therapeutic procedure in the management of infertility in females. Easy availability and accessibility of ultrasound in all primary health care centers definitely can prove superior to conventional method of diagnosis of tubal patency in such patient.